Pseudoaneurysm of the left ventricle. - Mackenzie, J W (1994)
Pseudoaneurysm of the left ventricle most often occurs after transmural myocardial infarction but may also follow cardiac operations, trauma, inflammation, or infection. In contrast to patients with true ventricular aneurysm, those with false aneurysm most commonly die of hemorrhage. Review of the reported surgical experience and of our 14 cases confirms that standard chest radiographs with an abnormal cardiac silhouette and rapidly expanding size may alert the physician to this sometimes overlooked diagnosis. Noninvasive tests such as color-flow Doppler echocardiography, 2-dimensional echocardiography, cineangiographic computed tomography, and transesophageal echocardiography allow relatively easy recognition of these apparently rare lesions with increasing frequency. Cardiac catheterization, however, is usually still necessary for a clear picture of the location and anatomy of the aneurysm and the state of the coronary arteries. Finally, a new classification is proposed, consisting of true aneurysm, false aneurysm, pseudo-false aneurysm, and mixed aneurysm.